Bike-sharing mobility patterns: a data-driven analysis for the city of Lisbon - Albuquerque, Vitória (2021)
Albuquerque, V., Andrade, F., Ferreira, J. C., Dias, M. S., & Bacao, F. (2021). Bike-sharing mobility patterns: a data-driven analysis for the city of Lisbon. EAI Endorsed Transactions on Smart Cities, 5(16), 1-20. [169580]. https://doi.org/10.4108/eai.4-5-2021.169580